2017
DOI: 10.1177/2055217317710829
|View full text |Cite
|
Sign up to set email alerts
|

Effects of expiratory muscle strength training on maximal respiratory pressure and swallow-related quality of life in individuals with multiple sclerosis

Abstract: BackgroundWeakening and dyscoordination of expiratory muscles in multiple sclerosis (MS) can impair respiratory and swallow function.ObjectiveThe objective of this paper is to test a novel expiratory muscle strength training (EMST) device on expiratory pressure, swallow function, and swallow-related quality-of-life (SWAL-QOL) in individuals with MS.MethodsParticipants with MS were randomized to a five-week breathing practice of either positive pressure load (EMST) or near-zero pressure (sham). We compared base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 35 publications
1
24
0
2
Order By: Relevance
“…Extending from more recent studies in patients with amyotrophic lateral sclerosis (ALS) and other neurodegenerative processes, we investigated the role of targeted exercise in ameliorating symptoms in the cystinosis population. The impact of EMST in this cohort is similar to that reported in patients with ALS, Parkinsons disease, and multiple sclerosis 32,41‐44 . In the interventional phase of this study, patients with more severe dysphagia showed modest improvements in the PAS score.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Extending from more recent studies in patients with amyotrophic lateral sclerosis (ALS) and other neurodegenerative processes, we investigated the role of targeted exercise in ameliorating symptoms in the cystinosis population. The impact of EMST in this cohort is similar to that reported in patients with ALS, Parkinsons disease, and multiple sclerosis 32,41‐44 . In the interventional phase of this study, patients with more severe dysphagia showed modest improvements in the PAS score.…”
Section: Discussionsupporting
confidence: 80%
“…The impact of EMST in this cohort is similar to that reported in patients with ALS, Parkinsons disease, and multiple sclerosis. 32,[41][42][43][44] In the interventional phase of this study, patients with more severe dysphagia showed modest improvements in the PAS score. This may suggest a benefit in more severely affected patients or indicate that the conventional scoring lacks the sensitivity to capture dysphagia in more mildly affected patients.…”
Section: Discussionmentioning
confidence: 85%
“…More recently, Tarameshlu et al 11 conducted a randomized controlled trial of traditional therapy (rehabilitation techniques) versus standard care (adaptation and compensation) on swallowing function. Moreover, a randomized controlled trial by Silverman et al 12 studied the effect of expiratory muscle strength training versus a sham condition on swallowing QOL. However, the methods of the found studies are patients with moderate-to-severe MS.…”
Section: Treatmentmentioning
confidence: 99%
“…The number of studies reporting on respiratory muscle strength training in persons with MS has been increasing in the past decade. A randomized controlled trial 12 with a focus on dysphagia concluded that expiratory muscle strength training with resistance leads to improved swallowing safety and improved swallowing coordination. Again, the group of participants was small, and long-term effects are unknown.…”
Section: Diagnostic Evaluationmentioning
confidence: 99%
“…A well-known rehabilitation technique to improve cough function is expiratory muscle strength training (EMST). Recently, the use of EMST has been evaluated in several studies, 15 including different patient groups such as Parkinson's disease, 14,16,17 multiple sclerosis, 18 sleep apnea, 19 head and neck cancer patients with dysphagia, 20 stroke, 21,22 amyotrophic lateral sclerosis, 23 supracricoid partial laryngectomy, 24 and healthy participants. [25][26][27] In several populations, to date, EMST has been shown to increase expiratory pressure generation by 30% to 150%, with an average increase of approximately 50% in a 4-week period of time.…”
Section: Introductionmentioning
confidence: 99%